2021
DOI: 10.1039/d1dt01827b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular copper iodide clusters: a distinguishing family of mechanochromic luminescent compounds

Abstract: This perspective describes the survey of the family of mechanochromic luminescent cubane copper iodide clusters. Studies of their mechanochromic luminescence properties are presented along with investigations to elucidate the underlying mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 159 publications
(146 reference statements)
0
31
0
Order By: Relevance
“…This can allow thermal population of the lowest energy excited singlet state (S 1 ) from the lowest energy triplet excited state (T 1 ), via a reverse intersystem crossing (RISC) inducing efficient radiative relaxation to the ground state and exalted solid‐state luminescence properties that occurs ideally at temperatures close to room temperature (RT). Importantly, this phenomenon is not only observed for mononuclear Cu(I) complexes but several polynuclear Cu I complexes have been also reported with enhanced solid‐state luminescent properties [5b,9n–x, 10d–j] . In such derivatives non‐covalent short intermetallic cuprophilic interactions (d(Cu−Cu) bellow ca.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…This can allow thermal population of the lowest energy excited singlet state (S 1 ) from the lowest energy triplet excited state (T 1 ), via a reverse intersystem crossing (RISC) inducing efficient radiative relaxation to the ground state and exalted solid‐state luminescence properties that occurs ideally at temperatures close to room temperature (RT). Importantly, this phenomenon is not only observed for mononuclear Cu(I) complexes but several polynuclear Cu I complexes have been also reported with enhanced solid‐state luminescent properties [5b,9n–x, 10d–j] . In such derivatives non‐covalent short intermetallic cuprophilic interactions (d(Cu−Cu) bellow ca.…”
Section: Introductionmentioning
confidence: 92%
“…So far, in the field of mechanochromic materials, the majority of systems that have been reported are organic dyes [5a,6] and gold [7a–k] and platinum [7l–r] metal‐based compounds [5b] which show a rich variety of mechanochromic properties. In this field, the development of mechanochromic luminescent Cu I coordination complexes offers particularly appealing perspectives for upcoming developments not only because of the low cost and relatively high abundance of copper but also due to the fascinating and various photophysical properties these complexes can exhibit [5b,8,9,10] . The emission behaviors of Cu I complexes are indeed characterized by the large diversity of the radiative relaxation processes involved with a rising attention being paid to derivatives exhibiting Thermally Activated Delayed Fluorescence (TADF) [8f,g,9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results indicated that the weak πacid•••base interactions existed between the Cu unit and the carbazole group and the Cu•••Cu interactions played an important role for their turn-on mechanochromism. For tetranuclear Cu(I) complexes, there were many factors that might affect the mechanochromism, such as the change of the Cu•••Cu distance, π-π interactions and the complex geometry (Benito et al, 2014;Peng et al, 2020;Utrera-Melero et al, 2020;Perruchas, 2021). In 2020, Hu's group discovered a supersalt-type Cu(I)-thiolate cluster with irreversible mechanochromism for the first time, which was not completely caused by the CA phase transition (Hu et al, 2020).…”
Section: Multinuclear Cu(i) Complexes With Mechanochromismmentioning
confidence: 99%
“…A stand out Cu(I) halide complex, is the molecular cubane cluster formulated [Cu4I4L4] (L = organic ligand). Its outstanding stimuli-responsive photoluminescent properties ranging from luminescence thermochromism, [26][27][28][29][30][31] mechanochromism, 32 solvatochromism [33][34][35][36] to rigidochromism, [37][38][39] are particularly appealing to access original multifunctional materials. Promising perspectives of applications have been already demonstrated with the development of inks based on [Cu4I4L4] clusters 40 and phosphors 41 or emitters for lighting devices.…”
Section: Introductionmentioning
confidence: 99%